An investigation of the $$α _S$$ α S and heavy quark mass dependence in the MSHT20 global PDF analysis - T. Cridge; L. A. Harland-Lang; A. D. Martin; R. S. Thorne (European Physical Journal C: Particles and Fields, 2021)
Abstract We investigate the MSHT20 global PDF sets, demonstrating the effects of varying the strong coupling $$α _S(M_Z^2)$$ α S ( M Z 2 ) and the masses of the charm and bottom quarks. We determine the preferred value, and accompanying uncertainties, when we allow $$α _S(M_Z^2)$$ α S ( M Z 2 ) to be a free parameter in the MSHT20 global analyses of deep-inelastic and related hard scattering data, at both NLO and NNLO in QCD perturbation theory. We also study the constraints on $$α _S(M_Z^2)$$ α S ( M Z 2 ) which come from the individual data sets in the global fit by repeating the NNLO and NLO global analyses at various fixed values of $$α _S(M_Z^2)$$ α S ( M Z 2 ) , spanning the range $$α _S(M_Z^2)=0.108$$ α S ( M Z 2 ) = 0.108 to 0.130 in units of 0.001. We make all resulting PDFs sets available. We find that the best fit values are $$α _S(M_Z^2)=0.1203± 0.0015$$ α S ( M Z 2 ) = 0.1203 ± 0.0015 and $$0.1174± 0.0013$$ 0.1174 ± 0.0013 at NLO and NNLO respectively. We investigate the relationship between the variations in $$α _S(M_Z^2)$$ α S ( M Z 2 ) and the uncertainties on the PDFs, and illustrate this by calculating the cross sections for key processes at the LHC. We also perform fits where we allow the heavy quark masses $$m_c$$ m c and $$m_b$$ m b to vary away from their default values and make PDF sets available in steps of $$Δ m_c =0.05~\mathrm GeV$$ Δ m c = 0.05 G e V and $$Δ m_b =0.25~\mathrm GeV$$ Δ m b = 0.25 G e V , using the pole mass definition of the quark masses. As for varying $$α _S(M_Z^2)$$ α S ( M Z 2 ) values, we present the variation in the PDFs and in the predictions. We examine the comparison to data, particularly the HERA data on charm and bottom cross sections and note that our default values are very largely compatible with best fits to data. We provide PDF sets with 3 and 4 active quark flavours, as well as the standard value of 5 flavours.